Unusual presentation of Kimura’s disease: a case series - Salunke, Aarti S.; Chavan, Ravindranath B.; Belgaumkar, Vasudha A.; Bhatt, Neelam (International Journal of Research in Dermatology, 2017)
Kimura’s disease is a rare chronic inflammatory disease of unknown etiology, presenting as painless subcutaneous nodules with lymphadenopathy and peripheral eosinophilia, mainly disturbing the head and neck region. It mainly affects Asian males in their 2nd to 4th decade of life. Kimura’s disease, although difficult to diagnose clinically, should be considered in the differential diagnosis of patients who have a primary lymphadenopathy with eosinophilia with or without subcutaneous nodules. It should be investigated accordingly as the disease has an indolent course and good prognosis. Herein we report two cases of Kimura’s disease, of which one had unusual site of involvement.